PENGARUH PEMBERIAN PUPUK KOTORAN KELINCI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KAILAN PADA TANAH ALLUVIAL - Yessy Anggrayni; Putu Dupa Bandem; Achmad Mulyadi Sirojul (Fakultas Pertanian Universitas Tanjungpura, 2013)
Kailan is one of the cabbage family vegetables to meet the nutritional needs of the community. Kailan on alluvial soil cultivation faced several obstacles, such as texture clay, topsoil is shallow, nutrient content and low organic matter and soil acidity level is high enough. One of the organic material that can be used to solve problems in the cultivation kailan alluvial soil is rabbit droppings. This study aimed to determine the effect of fertilizer and looking for the best rabbit dung and crop growth on soil aIluvial kailan. This study uses a pattern completely randomized design (CRD), which consists of 5 treatments and 5 replications. Each quiz consists of 4 samples of plants, so that a total number of 100 plants. The treatment in question is as follows: k0 = Without rabbit manure, k1 = 94 g/polybag rabbit manure, k2 = 446 g/polybag rabbit manure, k3 = 797 g/polybag rabbit manure, k4 = 1149 g/polybag rabbit manure. The variables measured were: leaf chlorophyll (spad unit), the top of the plant fresh weight (g), leaf area (cm2), root volume (cm3) and dry weight of plant (g). Provision of rabbit manure on crops kailan in alluvial soil significantly influenced all variables observations. The best results are indicated in the treatment with a dose k2 of 446 g/polybag for leaf chlorophyll content with the result of 45,76 spad unit, the top of the plant fresh weight by 19,44 g yield, leaf area to yield 14,14 cm2, root volume with results 4,4 cm3 and dry weight of plants to yield 5,68 g. Keywords: Kailan, Rabbit manure, Soil Alluvial